Transcriptional profiling of embryo cryotolerance - Marsico, Thamiris V.; Caetano, Diana P.; Rodrigues, Rafaela; Valente, Roniele S.; Fontes, Patricia K. [UNESP]; Mesquita, Fernando S.; Andrade, Sónia C. da Silva; Basso, Andréa C.; Nogueira, Marcelo F. G. [UNESP]; Sudano, Mateus J. (Wiley, 2020)
The cryosurvival of embryos is a complex process involving dynamic and integrated morphological, functional, and molecular changes. Here, we evaluated the transcriptional profiling of bovine embryos possessing high and low cryotolerance (HC and LC, respectively) by assessing the resumption of development. Embryos were produced in vitro (N = 1137) and cryopreserved (N = 894). Blastocysts samples possessed pronounced group individualization at RNA sequencing. A total of 114 genes were differentially expressed, and 27 and 84 genes were upregulated in HC and LC, respectively. Among the over-represented biological functions, cellular growth and proliferation, cell death and survival, and organismal survival were predicted to be activated, while cellular movement and cell-to-cell signaling were predicted to be inhibited in HC embryos. Enriched canonical pathways and upstream regulators related to cellular proliferation and survival (HC), inflammatory processes, and cell death (LC) were predicted to represent two embryonic molecular profiles present during the resumption of development after cryopreservation. The marked contrast in transcriptional profiles between HC and LC strongly suggests the influence of embryonic competence after cryopreservation on its respective transcriptome and indicated that HC and LC presented two different molecular strategies to overcome cryopreservation-related stress and resume postcryopreservation development.
Keywords: bovine; cryosurvival; embryonic competence; postcryopreservation resumption of development; quality